Dreams deferred: Contextualizing the health and psychosocial needs of undocumented Asian and Pacific Islander young adults in Northern California. (July 2017) - Sudhinaraset, May; Ling, Irving; To, Tu My; Melo, Jason; Quach, Thu
Abstract: There are currently 1.5 million undocumented Asians and Pacific Islanders (APIs) in the US. Undocumented API young adults, in particular, come of age in a challenging political and social climate, but little is known about their health outcomes. To our knowledge, this is the first study to assess the psychosocial needs and health status of API undocumented young adults. Guided by social capital theory, this qualitative study describes the social context of API undocumented young adults (ages 18–31), including community and government perceptions, and how social relationships influence health. This study was conducted in Northern California and included four focus group discussions (FGDs) and 24 in-depth interviews (IDIs), with 32 unique participants total. FGDs used purposeful sampling by gender (two male and two female discussions) and education status (in school and out-of-school). Findings suggest low bonding and bridging social capital. Results indicate that community distrust is high, even within the API community, due to high levels of exploitation, discrimination, and threats of deportation. Participants described how documentation status is a barrier in accessing health services, particularly mental health and sexual and reproductive health services. This study identifies trusted community groups and discusses recommendations for future research, programs, and policies. Highlights: This study describes API undocumented young adult psychosocial health needs. Low bonding and bridging social capital among API undocumented young adults. Community distrust high because of exploitation and threats of deportation. High mental health needs among API undocumented young adult population.